Modeling and Validating COBIT 5-Based It Governance ‎Capability in Automotive After-Sales Services: Empirical Insights from Authorized Dealerships - Kridiawan, Yuly; Legowo, Nilo; Soewito, Benfano; Lumban Gaol, Ford (International Journal of Basic and Applied Sciences, 2025)
The increasing adoption of digital technologies in automotive after-sales services has introduced new challenges for IT governance, particularly within authorized car dealerships. These dealerships rely on digital tools, such as customer relationship management (CRM), service ‎scheduling, and performance monitoring systems, to deliver consistent and effective services. As these systems become more complex, ‎structured IT governance is critical to ensure strategic alignment, risk management, and service quality.‎This study assesses the implementation and perceived effectiveness of IT governance practices using the COBIT 5 framework. The assessment model is based on its five core domains: Evaluate, Direct and Monitor (EDM); Align, Plan and Organize (APO); Build, Acquire and ‎Implement (BAI); Deliver, Service and Support (DSS); and Monitor, Evaluate and Assess (MEA). A total of 87 respondents from authorized car dealerships in Indonesia participated in a quantitative survey. Data were analyzed using Partial Least Squares Structural Equation ‎Modeling (PLS-SEM).‎The results indicate moderate governance maturity across all domains, with the highest capability observed in EDM (mean = 3.6) and the ‎lowest in MEA (mean = 2.9). Important path links between domains support the structural reasoning of the COBIT 5 model. This paper ‎offers empirical analysis on COBIT 5 implementation in customer-facing automotive environments as well as pragmatic advice for improving IT governance, service delivery, and performance measurement in after-sales operations. While the findings provide valuable insights, ‎they are contextually limited to authorized dealerships in Indonesia and may vary in other regions with different governance practices or IT ‎maturity‎.
Keywords: IT Governance; After-Sales Services; Authorized Dealership; Cobit-5; Capability Assessment